Objeción literaria al empirismo de David Hume - Botero Camacho, Manuel José (Estudios Ingleses de la Universidad Complutense, 2006)
The present article proposes a reading of the short story titled “Tlön, Uqbar, Orbis Tertius” by the Argentinan writer Jorge Luis Borges (1899-1986). Guided by the philosophical premises expounded by David Hume (1771-1776) in his works A Treatise of Human Nature and Enquiry Concerning Human Understanding, the idea means to find in the short story a re writing of the logical structure of Hume´s theories. The fiction piece is an objection and a reductio absurdum of the philosophers exposition and conclusions (those that propose an impossibility of relating to the outside world, the links of causality or even to give one step outside our minds). This article is a trip through the world that would remain if Hume had been right in the development of his works; it is a set up of that world, which in the end is a world of linguistic fiction.